Expression of C19MC miRNAs in HCC associates with stem-cell features and the cancer-testis genes signature. Issue 6 (June 2018) - Augello, Claudia; Colombo, Federico; Terrasi, Andrea; Trombetta, Elena; Maggioni, Marco; Porretti, Laura; Rossi, Giorgio; Guerneri, Silvana; Silipigni, Rosamaria; Bosari, Silvano; Vaira, Valentina
Abstract: Background: Intratumor heterogeneity of hepatocellular carcinoma (HCC) and, among HCC cell subsets, the cancer stem cell population (hCSC), is responsible for therapeutic resistance and disease relapse. Aims: To characterize hCSC-enriched HCCs at the molecular level. Methods: Side population (SP) was used to identify the hCSCs in multiple tumor sampling from different patients and primary HCCs cultures. FACS was used to immunoprofile cultures. miRNAs were profiled in samples and correlated to SP. The Cancer Genome Atlas (TCGA) HCC dataset was analyzed to search for signatures associated with C19MC miRNAs expression. Results were confirmed by immunohistochemistry. Results: The miRNA cluster on chromosome 19 (C19MC) was enriched in SP and in HCCs with a high SP fraction. At the molecular level, an elevated C19MC was correlated with expression of precursor transcripts. In TCGA-HCC series, high C19MC expression identified a subset of patients with poorer prognosis, advanced disease and overexpression of the cancer-testis (CT) antigens. These data were confirmed in an independent cohort of HCCs and at the protein level. Conclusion: C19MC miRNAs and CT antigens overexpression represents a novel oncogenic pathway in a subset of hCSC-enriched HCCs with dismal prognosis. CT antigens are promising immunotherapy targets. Therefore, these molecular signatures could identify HCCs who could benefit from immunotherapy.